Clinical Test Instrument Development to Identify and Track Recovery from Concussion - Bene, Edina Reka; Sepulveda, Amanda M. (Seminars in Speech and Language, 2014)
Over the past 25 years, neuropsychological assessment has been the prominent clinical method for evaluating neurocognitive functioning and monitoring recovery following mild traumatic brain injury (mTBI), or concussion. During this time, neuropsychological assessment of concussion has developed extensively starting from traditional paper-and-pencil tests to the more current computerized assessment batteries that are specifically designed for evaluating mTBI. Concussion assessment is complex and challenging due to the highly variable neurocognitive behavior and the wide range of diverse symptoms that follow an injury. Therefore, neuropsychological testing is only one component of a multifaceted, comprehensive assessment approach that also includes balance testing and symptom assessment. Because concussions may go undetected, more emphasis has been placed on objective and sensitive neuropsychological measures. Factors that could affect the validity of test performance include athletes not recognizing or intentionally hiding their symptoms or sandbagging their baseline performance. Due to the complex nature of identifying and evaluating mild head injuries, the purpose of this review is to discuss (1) the clinical use of neuropsychological testing in concussion management, (2) the methods used for evaluating and monitoring recovery following concussion, (3) the characteristics of current assessment instruments, and (4) additional clinical factors and approaches for concussion assessment and management.
Keywords: Neuropsychological assessment; concussion; adults; multimodal assessment; computerized test batteries